INTERNATIONAL TOURISM MARKET AND ITS ADVANTAGES - Radjapova Nasiba Makhmudjonovna (Bright Mind Publishing, 2025)
This academic article analyzes how the tourism industry is developing globally and its economic, cultural, environmental and social aspects. The article examines in detail the main players in the international tourism market, its economic and social benefits, as well as the challenges it faces and ways to overcome these challenges. The article highlights the importance of policies, innovations and international cooperation needed to ensure the sustainable development of global tourism. It also puts forward proposals such as digitizing tourism, developing eco-tourism and supporting local populations. This article provides useful information for researchers, practitioners and policymakers in the field of tourism.
Keywords: International tourism market, cultural exchange, ecological tourism, eco-tourism, tourism policy.